A Typology of Shop Stewards: A Confirmatory Factor Analysis - Reshef, Yonatan (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1987)
In this study, a typology of shop steward modes of role behavior was developed and tested. Three ideal types of role behavior — passive, cooperative, and radical — were derived based on a theoretical framework consisting of Marxist, pluralist, and structural-functionalist approaches. Two behavioral modes were added to the theoretical typology to provide for the possibilities offailed and erratic stewardhip styles. The five role behaviors were subjected to confirmatory factor analysis resulting in a four-facet behavioral typology. The typology and its measuring tool can be used to generate and guide future research.